Fumigant Toxicity of Five Essential Oils Against the Eggs of Ephestia kuehniella Zeller and Plodia interpunctella (Hⁿbner) (Lepidoptera: Pyralidae) - Ayvaz, Abdurrahman; Karaborklu, Salih; Sagdic, Osman (Asian Journal of Chemistry, 2010)
The ovicidal activity of five essential oil vapours distilled from savory Satureja thymbra L., laurel Laurus nobilis L., myrtle Myrtus communis L., lemon Citrus limon L. and marjoram Origanum majorana L. were tested against of two stored-product moths namely the Indian meal moth Plodia interpunctella and the Mediterranean flour moth, Ephestia kuehniella. Of all the samples tested, the essential oil obtained from savory produced 100 % mortality for the eggs of both E. kuehniella and P. interpunctella. The highest mortalities caused by essential oils of myrtle, laurel, marjoram and lemon were 57.50, 45.83, 42.50 and 27.50 % for E. kuehniella eggs and were 41.66, 50.83, 57.50 and 26.66 % for P. interpunctella eggs, respectively. At the moderate dose (50 μL/L air) the LT99 values of the most effective essential oil savory were 158.50 and 81.88 h for the eggs of E. kuehniella and P. interpunctella, respectively.